Heave and Pitch Motion Performances of a Ship Towing System Incorporated with Symmetrical Bridle Towline Model - Ahmad Fitriadhy; Nur Adlina Aldin; Nurul Aqilah Mansor; Nur Aqilah Hanis Zalizan (EPI International Journal of Engineering, 2019)
An investigation on vertical motion characteristics of a ship towing system incorporated with symmetrical bridle towline configuration set a real challenge for the naval architect engineer. This paper presents a Computational Fluid Dynamic (CFD) approach to analyse heave and pitch motion performances in waves. Several towing parameters such as various towline length and towing’s velocity have been taken into account. Here, 1B (barge) is employed in the simulation; and designated as a towed ship. The results revealed that the subsequent increase of the towline lengths has been basically proportional with the increase of her heave motion; while inversely decrease in pitch motions. In addition, the effect of the extending towline length = 1.0 to 3.0 resulted in insignificant effect to the towline tension. However, the increase of the towing’s velocity from 0.509 m/s to 0.728 m/s has led to significantly increase her heave motion and the towline tension by 40.46% and 24%, respectively; meanwhile, the pitch motion barge has sufficiently decreased by 35.94%. This simulation has been beneficial for the towing operator to ensure a higher level of the safety navigation of ship towing system.